Determination of elements in thermal springs for monitoring pre-earthquake activites by ICP-MS - Yaman, Mehmet; Şaşmaz, Ahmet; Kaya, Gökçe; İnce, Muharrem; Karaaslan, Nagihan; Özcan, Cemile; Akkuş, Şükran (My University, 2011)
This study presents the results of hydrogeochemical studies carried out at the Kos thermal springs in Bingol, located in East Anatolia, Turkey. More than 250 thermal water samples were collected on a regular basis from November 2006 to January 2009 to measure element concentrations as a monitor of earthquake precursors. Water samples were analyzed using inductively coupled plasma mass spectrometry (ICP-MS). The B, Ba, Br, and Ge concentrations were monitored for three years and ranged from 6822–7666, 64–101, 271–406, and 4.1–6.0 ?g L-1, respectively. The chloride concentrations for this period were in the 89–127 mg L-1 range. The data identify some element anomalies at least two hours prior to a major earthquake and for some time afterwards. These anomalies are characterized by decreases up to 20% in B, Ba, Cl, and Ge concentrations and can be attributed to stress-/strain-induced pressure changes in the subsurface water systems. From this study, it can be suggested that thermal springs in a fault line area are ideal sites for monitoring precursors to earthquakes.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hydrogeochemistry; Thermal springs; Earthquakes; Trace element